2021
DOI: 10.3389/feart.2021.629826
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Estimation and Its Influencing Factors Based on Temporal Stability on a Semiarid Sloped Forestland

Abstract: Soil water content (SWC) plays a crucial role in the hydrological cycle and ecological restoration in arid and semi-arid areas. Studying the temporal stability of SWC spatial distribution is a requirement for the dynamic monitoring of SWC and the optimization of water resource management. The SWC in a Pinus tabulaeformis Carr. forest on the slope of the Loess Plateau of China were analyzed in five soil layers (0–100 cm with an interval of 20 cm) in the rainy and dry seasons from July 2014 to November 2017. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The higher SD, CV, and SDMR values indicate the lower SWC stability at the upper soil layer (Table 2). Due to the low SWC spatial variability in deeper soil layers, the MRD variation range tends to decrease with depth, regardless of the seasonal fluctuation [49]. Similar to previous research findings, the average SDRD values tend to decline as well with increasing soil depth [20,50].…”
Section: Swc Temporal Variability and Stabilitysupporting
confidence: 86%
“…The higher SD, CV, and SDMR values indicate the lower SWC stability at the upper soil layer (Table 2). Due to the low SWC spatial variability in deeper soil layers, the MRD variation range tends to decrease with depth, regardless of the seasonal fluctuation [49]. Similar to previous research findings, the average SDRD values tend to decline as well with increasing soil depth [20,50].…”
Section: Swc Temporal Variability and Stabilitysupporting
confidence: 86%
“…Average variability in S tn was similar at 0.35 m and 0.50 m depths. Previous studies have reported increasing variability with depth (Gao et al, 2015; Hu et al, 2010) and decreasing variability with depth (Cheng et al, 2017; Duan et al, 2017; Martinez et al, 2013; Xu et al, 2021). The difference between studies and soil properties, topography, and subsoil characteristics within each region are the reasons for the increase or decrease in soil moisture variability with depth that can explain the different conclusions obtained in other studies (Vanderlinden et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, there are studies in which higher variation in soil moisture was found in topsoil measurements (e.g. 0–0.20 cm) compared to the subsoil (0.20–0.50 m), for example, (Cheng et al, 2017; Duan et al, 2017; Martinez et al, 2013; Xu et al, 2021), and vice versa (Gao et al, 2015; Hu et al, 2010). These factors, meteorology/climatology, soil properties, and vegetation, affect the mean soil moisture mean and variance relation differently and might be intertwined depending on the region, scale of the study and measurement depth below the surface (Suo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation